Corporate Governance and the Investment Efficiency of Diversified Corporate Asset Buyers. Issue 1 (6th April 2017) - Chen, I‐Ju; Chen, Sheng‐Syan
Abstract : Many corporate assets are bought and sold each year in the U.S. and most scholars believe these transactions improve economic efficiency. But given the reality that the interests of corporate managers may diverge from those of their shareholders and reflect empire‐building or other managerial entrenchment strategies—and that such agency problems tend to be worse in highly diversified, multi‐divisional companies—the authors tested the proposition that diversified corporate asset buyers with more effective governance structures can be expected to allocate capital more efficiently, as reflected in higher rates of return on operating capital and more favorable market reactions to the announcements of their purchases. Using a sample of diversified U.S. companies that announced large asset purchases between 1988 and 2006, the authors report finding that the investment allocation process following such asset purchases was more consistent with value creation in the case of diversified buyers with more effective governance structures, which were identified by their greater board independence, higher‐quality audit committees, and higher levels of stock ownership by institutional ownership, directors, and CEOs.